Can Sperm Selection, Inseminating Dose, and Artificial Insemination Technique Influence Endometrial Inflammatory Response in Mares? - Gomes, Gustavo M.; Crespilho, André M.; Leão, Karen M.; Jacob, Júlio C.F.; Gomes, Letícia P.M.; Segabinazzi, Lorenzo G. [UNESP]; Papa, Frederico O. [UNESP]; Alvarenga, Marco A. [UNESP] (Elsevier, 2019)
The aim of this study was to investigate the influence of sperm concentration, sperm quality, and semen deposition site on uterine inflammatory response in mares. Twenty-five mares with healthy reproductive tracts were used for artificial inseminations (AIs) using frozen-thawed semen and divided into 5 experimental groups: Control—insemination with 800 × 106 total spermatozoa in the body of the uterus (n = 5); G2—insemination with 40 × 106 total motile sperm (TMS) into uterine body (n = 5); G3—insemination with 40 × 106 TMS at the uterotubal junction by hysteroscopy (HI) (n = 5); G4—insemination with 40 × 106 TMS at the uterotubal junction by HI, with frozen-thawed semen selected by Percoll gradient (n = 5); G5—insemination with 40 × 106 total motility sperm into uterine body, using frozen-thawed semen selected by Percoll gradient (n = 5). Number of polymorphonuclear neutrophils in uterine cytology was observed at 8 and 24 hours after AI. A reduced inflammatory endometrial reaction (P <.05) was observed, both at 8 and 24 hours, in mares inseminated with low sperm dose (40 × 106) compared with those inseminated with regular semen dose (800 × 106), with the exception of G4 that did not differ from the control group. Sperm selection by Percoll gradient did not influence the intensity of endometrial inflammatory response (P >.05) regardless of the type of insemination (conventional or hysteroscopic). In addition, mares inseminated by hysteroscopy showed a greater local inflammatory reaction (P <.05) in relation to those inseminated into uterine body. In conclusion, reduction of sperm insemination dose may be an alternative method to decrease endometrial inflammatory response in mares. However, hysteroscopic insemination and the current protocols used for sperm selection by Percoll did not show efficient results to reduce endometrial inflammation in mares. Further studies about sperm selection and HI insemination techniques are necessary to determine the benefits and the appropriate protocol to be performed in barren mares.
Keywords: Barren mares; Endometritis; Hysteroscopic; Low insemination dose; Sperm selection